It’s A Match: Strategi Pengurangan Ketidakpastian oleh Pengguna Perempuan di Aplikasi Kencan Online Bumble - Hana' Hamidah Sahid (PERSPEKTIF, 2023)
Every interpersonal relationship always goes through a stage of reducing uncertainty so that an interpersonal relationship can develop. This includes interpersonal relationships in online dating applications. This study examines the strategies used by female users to reduce the uncertainty in online dating application Bumble. Bumble was chosen as it’s the only online dating application that put woman in charge to make the first move. Uncertainty reduction theory was used to analyse the findings. Three informants were interviewed and literature studies from previous studies in similar topics were used to gain further information. The result shows that each informant has different approach and strategies to reduce the uncertainty while using online dating application Bumble. The strategies help each informant to decide whether to continue or stop the interaction while using Bumble.